The Influence of E-Learning on Teaching Administration of Primary Education in Rwanda (International Journal of Scientific Research and Management (IJSRM), 2022)
The development of information technology (e-Learning) has a potential to support the learning process revolution; in this matter, a research is to be carried out to assess the impact of e-Learning on the teaching and learning management in primary education in Rwanda. The researcher must test the validity of the learning using expert validation sheet instruments and limited testing using observation sheets, interview guides, questionnaires and documentation as the main instruments. Data analysis will be collected using descriptive analysis techniques. E-learning is able to generate a high attractiveness and high learning motivation for the students. Learning is more fun so that students learn more optimally and effectively. The main thesis is that E-learning spawns numerous problems for primary students—namely a homogenization and dehumanization. This ultimately leads to what Ritzer (2000) calls a ‘Mc Donaldisation of education’ Key words: E-Learning, Teaching Management. INTRODUCTION